Genome-Wide Association Study Identifies Eight Novel Loci for Susceptibility of Scrub Typhus and Highlights Immune-Related Signaling Pathways in Its Pathogenesis - Yong-Chan Kim; Soriul Kim; Hee-Kwon Kim; Yi Lee; Chol Shin; Chang-Seop Lee; Byung-Hoon Jeong (Cells, 2021)
Scrub typhus is a fatal zoonotic disease caused by Orientia tsutsugamushi. This disease is accompanied by systemic vasculitis, lymphadenopathy, headache, myalgia, and eschar. In recent studies, a novel strain that is resistant to current medical treatment was identified in Thailand. Thus, the development of new specific drugs for scrub typhus is needed. However, the exact molecular mechanism governing the progression of scrub typhus has not been fully elucidated. To understand disease-related genetic factors and mechanisms associated with the progression of scrub typhus, we performed a genome-wide association study (GWAS) in scrub typhus-infected patients and found a scrub typhus-related signaling pathway by molecular interaction search tool (MIST) and PANTHER. We identified eight potent scrub typhus-related single nucleotide polymorphisms (SNPs) located on the PRMT6, PLGLB2, DTWD2, BATF, JDP2, ONECUT1, WDR72, KLK, MAP3K7, and TGFBR2 genes using a GWAS. We also identified 224 genes by analyzing protein-protein interactions among candidate genes of scrub typhus and identified 15 signaling pathways associated with over 10 genes by classifying these genes according to signaling pathways. The signaling pathway with the largest number of associated genes was the gonadotropin-releasing hormone receptor pathway, followed by the TGF-beta signaling pathway and the apoptosis signaling pathway. To the best of our knowledge, this report describes the first GWAS in scrub typhus.